Characteristic Curve of a Fuel Cell - Muzamir, Isa; Baharuddin, Ismail; Che Mat Hadzer; Ismail, Daut; Faizah, Abu Bakar (Science Publications, 2008)
Link to publisher's homepage at http://scipub.org/scipub/index.php